Urgensi Instruksi Presiden Nomor 01 Tahun 2025 terhadap pelaksanaan APBN di Kementerian/Lembaga Tahun 2025 - Hartono, Hasim (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Urgency of Presidential Instruction Number 01 of 2025 on the Implementation of the State Budget in Ministries/Institutions in 2025, This study aims to determine the supporting factors for the budget efficiency program and to determine the impact on the implementation of the State Budget in the Ministry and Institution environment. This study uses a normative legal method. This study will examine in depth the relevant legal texts, including laws, government regulations, and related policies. The results obtained from this study are that Presidential Instruction Number 01 of 2025 is a strategic step by the government in managing state spending more effectively, while reducing the fiscal deficit which is projected to reach IDR 616.2 trillion or 2.53 percent of GDP. The government's budget efficiency in 2025 includes cutting ministry and institution spending by IDR 256.1 trillion and cutting transfers to regions by IDR 50.59 trillion, according to the Minister of Finance's Letter Number S-37/MK.02/2025. The 2025 budget efficiency is supported by several factors, including: Paying maturing foreign debt; The Free Nutritious Meal Program (MBG) which absorbs a large budget and the Flexible Work System implemented in several ministries and institutions. Budget Efficiency for Ministries and Institutions has an impact on spending items, including reducing the cost of office stationery, business travel, vehicle rentals, and ceremonial activities. The 2025 budget efficiency has a significant impact on various investment sectors, especially infrastructure, hospitality, tourism, and consumer goods.